Variation in the design of Do Not Resuscitate orders and other code status options: a multi-institutional qualitative study. Issue 8 (20th October 2020) - Batten, Jason N; Blythe, Jacob A; Wieten, Sarah; Cotler, Miriam Piven; Kayser, Joshua B; Porter-Williamson, Karin; Harman, Stephanie; Dzeng, Elizabeth; Magnus, David
Abstract : Background: US hospitals typically provide a set of code status options that includes Full Code and Do Not Resuscitate (DNR) but often includes additional options. Although US hospitals differ in the design of code status options, this variation and its impacts have not been empirically studied. Design and methods: Multi-institutional qualitative study at 7 US hospitals selected for variability in geographical location, type of institution and design of code status options. We triangulated across three data sources (policy documents, code status ordering menus and in-depth physician interviews) to characterise the code status options available at each hospital. Using inductive qualitative methods, we investigated design differences in hospital code status options and the perceived impacts of these differences. Results: The code status options at each hospital varied widely with regard to the number of code status options, the names and definitions of code status options, and the formatting and capabilities of code status ordering menus. DNR orders were named and defined differently at each hospital studied. We identified five key design characteristics that impact the function of a code status order. Each hospital's code status options were unique with respect to these characteristics, indicating that code status plays differing roles in each hospital. Physician participants perceived that the design of code status options shapes communication and decision-making practices about resuscitation and life-sustaining treatments, especially at the end of life. We identified four potential mechanisms through which this may occur: framing conversations, prompting decisions, shaping inferences and creating categories. Conclusions: There are substantive differences in the design of hospital code status options that may contribute to known variability in end-of-life care and treatment intensity among US hospitals. Our framework can be used to design hospital code status options or evaluate their function.